RISE: Achieving a sustainable lipid reduction via systematic screening / Farhana Fakhira Ismail - Ismail, Farhana Fakhira (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Whether your blood lipid levels are high or low, you will experience the same symptoms. This is because lipid abnormalities will not show any noticeable signs or symptoms. The presence of lipid abnormalities is a significant risk factor for coronary heart disease (CHD). You are considered to have lipid abnormalities when you have abnormal values for cholesterol indices which are high total cholesterol (TC), high level of low-density lipoprotein (LDL), high triglyceride (TG) or low level of high-density lipoprotein (HDL).